Expanding the Toolbox for Genetic Manipulation in Pseudogymnoascus: Rnai-Mediated Silencing and Crispr/Cas9-Mediated Disruption of a Polyketide Synthase Gene Involved in Red Pigment Production in P. Verrucosus - Chavez-Rosales, R; Gil-Duran, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Fungi belonging to the genus Pseudogymnoascus have garnered increasing attention in recent years. One of the members of the genus, P. destructans, has been identified as the causal agent of a severe bat disease. Simultaneously, the knowledge of Pseudogymnoascus species has expanded, in parallel with the increased availability of genome sequences. Moreover, Pseudogymnoascus exhibits great potential as a producer of specialized metabolites, displaying a diverse array of biological activities. Despite these significant advancements, the genetic landscape of Pseudogymnoascus remains largely unexplored due to the scarcity of suitable molecular tools for genetic manipulation. In this study, we successfully implemented RNAi-mediated gene silencing and CRISPR/Cas9-mediated disruption in Pseudogymnoascus, using an Antarctic strain of Pseudogymnoascus verrucosus as a model. Both methods were applied to target azpA, a gene involved in red pigment biosynthesis. Silencing of the azpA gene to levels of 90% or higher eliminated red pigment production, resulting in transformants exhibiting a white phenotype. On the other hand, the CRISPR/Cas9 system led to a high percentage (73%) of transformants with a one-nucleotide insertion, thereby inactivating azpA and abolishing red pigment production, resulting in a white phenotype. The successful application of RNAi-mediated gene silencing and CRISPR/Cas9-mediated disruption represents a significant advancement in Pseudogymnoascus research, opening avenues for comprehensive functional genetic investigations within this underexplored fungal genus. © 2024 by the authors.